Active Therapeutic and Diagnostic Management of Acute Appendicitis in a Pregnant Woman During the First Trimester - M.Yu. Akramova; A.Sh. Abdumajidov; K.F. Zuparov; O.O. Alimxanov; Z.A. Aslonov (Academia Open, 2026)
General Background: Acute appendicitis is a frequent cause of abdominal pain in women of reproductive age and presents diagnostic and therapeutic challenges during pregnancy due to anatomical and physiological changes. Specific Background: In the first trimester, symptoms may appear typical, yet clinical evaluation remains complex, requiring careful diagnostic and surgical decision-making to ensure maternal and fetal safety. Knowledge Gap: Despite established surgical approaches, the optimal management strategy for appendicitis in early pregnancy, particularly regarding minimally invasive techniques and multidisciplinary care, remains insufficiently detailed in clinical case-based evidence. Aims: This study aims to present a clinical case and evaluate diagnostic and therapeutic management of acute appendicitis in a pregnant woman during the first trimester. Results: A 28-year-old patient at 12 weeks of gestation underwent successful laparoscopic appendectomy following clinical, laboratory, and ultrasound diagnosis, with uneventful postoperative recovery and preserved pregnancy confirmed by follow-up. Novelty: The study highlights the integration of laparoscopic surgery with obstetric collaboration and tailored postoperative care in early pregnancy. Implications: Early diagnosis, interdisciplinary management, and minimally invasive intervention contribute to favorable maternal and fetal outcomes while preventing severe complications such as perforation and peritonitis. Highlights:• Early Surgical Intervention Prevented Progression to Severe Abdominal Complications• Multidisciplinary Coordination Ensured Safe Perioperative Management for Mother and Fetus• Minimally Invasive Approach Supported Rapid Recovery and Stable Gestational Continuation Keywords: Acute Appendicitis, Pregnancy, Laparoscopic Appendectomy, First Trimester, Surgical Management.